Identification of inflammatory markers in eosinophilic cells of the immune system: fluorescence, Raman and CARS imaging can recognize markers but differently - Borek-Dorosz, Aleksandra; Grosicki, Marek; Dybas, Jakub; Matuszyk, Ewelina; Rodewald, Marko; Meyer-Zedler, Tobias; Schmitt, Michael; Popp, Jürgen; Malek, Kamilla; Baranska, Malgorzata (Cellular and Molecular Life Sciences, 2022)
Eosinophils (Eos) play an important role in the immune system’s response releasing several inflammatory factors and contributing to allergic rhinitis, asthma, or atopic dermatitis. Since Eos have a relatively short lifetime after isolation from blood, usually eosinophilic cell line (EoL-1) is used to study mechanisms of their activation and to test therapies. In particular, EoL-1 cells are examined in terms of signalling pathways of the inflammatory response manifested by the presence of lipid bodies (LBs). Here we examined the differences in response to inflammation modelled by various factors, between isolated human eosinophils and EoL-1 cells, as manifested in the number and chemical composition of LBs. The analysis was performed using fluorescence, Raman, and coherent anti-Stokes Raman scattering (CARS) microscopy, which recognised the inflammatory process in the cells, but it is manifested slightly differently depending on the method used. We showed that unstimulated EoL-1 cells, compared to isolated eosinophils, contained more LBs, displayed different nucleus morphology and did not have eosinophilic peroxidase (EPO). In EoL-1 cells stimulated with various proinflammatory agents, including butyric acid (BA), liposaccharide (LPS), or cytokines (IL-1β, TNF-α), an increased production of LBs with a various degree of lipid unsaturation was observed in spontaneous Raman spectra. Furthermore, stimulation of EoL-1 cells resulted in alterations of the LBs morphology. In conclusion, a level of lipid unsaturation and eosinophilic peroxidase as well as LBs distribution among cell population mainly accounted for the biochemistry of eosinophils upon inflammation.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Coherent anti-Stokes Raman scattering (CARS); EoL-1 cells; Fluorescence microscopy; Primary isolated eosinophils (Eos); Spontaneous Raman spectroscopy